Plasmic Degradation of Crosslinked Fibrin: CHARACTERIZATION OF NEW MACROMOLECULAR SOLUBLE COMPLEXES AND A MODEL OF THEIR STRUCTURE - Francis, Charles W. (1980)
Crosslinked fibrin was digested by plasmin, and three soluble complexes larger than DD/E were purified and characterized. After gel filtration chromatography, the purified complexes were shown to have molecular weights of 465,000, 703,000, and 850,000, as determined by equilibrium sedimentation. Each of the complexes was dissociated into two or more fragments by SDS-polyacrylamide gel electrophoresis. The structure of these subunit fragments was deduced from determinations of their molecular weights and polypeptide chain composition and from known sites of plasmin cleavage of fibrin. Fragments larger than DD have been identified that contain intact γγ crosslinks as well as fragments resulting from cleavages at or near this site. The former include DY (mol wt 247,000), YY (mol wt 285,000), DXD (mol wt 461,000), and YXD (mol wt 500,000); and the latter include fragments XD (mol wt 334,000) and XY (mol wt 391,000). A schematic model was developed to explain the structure of the large noncovalently bound complexes based on their molecular weight and observed component fragments. Our scheme supports the two-stranded half-staggered overlap model as the basic unit of fibrin structure, in which each complex consists of fragments from two adjacent complementary antiparallel fibrin strands. The smallest derivative, complex 1, is the DD/E complex; complex 2 contains apposed DY and YD fragments, and complex 3 consists of fragments DXD and YY. Complex 4 is less well-characterized, but its intact structure is projected to consist of YXD and DXY fragments from adjacent fibrin strands. Each complex is heterogeneous in subunit composition, reflecting additional plasmin cleavages within and/or adjacent to its theoretical boundaries. Since most of the protein initially released into solution from degrading fibrin is as complexes larger than DD/E, the derivatives described in this report are likely to be major circulating degradation products of crosslinked fibrin in vivo.